2022
DOI: 10.1200/jco.2022.40.16_suppl.4552
|View full text |Cite
|
Sign up to set email alerts
|

Baseline circulating soluble factors as predictors of response to nivolumab in metastatic clear cell renal cell carcinoma (mRCC): A validation study within the NIVOREN GETUG-AFU 26 translational study.

Abstract: 4552 Background: The NIVOREN GETUG-AFU 26 study launched a translational research program to quantify baseline circulating soluble factors levels and correlate them with outcomes to nivolumab in mRCC pts. We previously identified on a training set (n = 80, 40 responders/40 progressors) several soluble factors significantly associated with worse overall survival (OS), progression-free survival (PFS) and response (IL-8 and VEGF), or with worse OS only (IL-6, IL-7) (Carril-Ajuria et al. ASCO GU. 2022). Our aim w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…A pilot study of metastatic RCC showed that tremelimumab with and without cryoablation increased TLS formation in patients with clear cell histology compared with baseline (196). In another study using nivolumab in patients with metastatic RCC, a significant enrichment of TLS was observed in responders rather than non-responders, showing a trend for improved outcomes (199). Similarly, Ho et al reported the results of a single-arm phase 1b trial of neoadjuvant cabozantinib and nivolumab in patients with locally advanced HCC.…”
Section: Clinical Trials Related To Tlsmentioning
confidence: 97%
“…A pilot study of metastatic RCC showed that tremelimumab with and without cryoablation increased TLS formation in patients with clear cell histology compared with baseline (196). In another study using nivolumab in patients with metastatic RCC, a significant enrichment of TLS was observed in responders rather than non-responders, showing a trend for improved outcomes (199). Similarly, Ho et al reported the results of a single-arm phase 1b trial of neoadjuvant cabozantinib and nivolumab in patients with locally advanced HCC.…”
Section: Clinical Trials Related To Tlsmentioning
confidence: 97%